Expression of pan-B cell markers by tumor cells in different types of classical Hodgkin Lymphoma - Gurtovyy, V. A. (Pathologia, 2013)
In the study estimation of anti-B cell markers (CD20, CD79α) and evaluation of their possible prognostic importance in different types of classic Hodgkin Lymphoma were performed. It was shown that CD20 and CD79α expression took place less then in 20% and 10% cases respectively and it was only in some tumor cells. It was determined that expression of anti-B cell markers are not useful in classic Hodgkin Lymphoma diagnostics and could not prognosticate clinical course.